Measuring the Impact of Socially Responsible Supply Chains on Firm Performance - Sharma, Satyendra; Chadha, Saurabh; Dhar, Shombit (Prabandhan: Indian Journal of Management, 2018)
Most supply chain managers in the world optimize supply chains by helping different stakeholders in supply chains. Traditionally, business firms optimize the performance and compromise their pay-offs in order to increase profits (by lowering cost) of the entire supply chain. However, recent literature has hinted at another dimension to improving performance for companies by having socially responsible supply chains that take into consideration the triple bottom line approach. Literature has discussed the conceptual frameworks and empirical studies on supply chain sustainability, but there is a lack of studies on the effect of socially responsible supply chain practices on business performance. This research paper aimed at understanding the impact of having supply chains that are socially responsible and used the event study methodology to understand the impact of socially responsible supply chains on companies' performance.